Principles of Food Chemistry - deMan, John M.; Finley, John W.; Hurst, W. Jeffrey; Lee, Chang Yong.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
Completely revised, this new edition updates the chemical and physical properties of major food components including water, carbohydrates, proteins, lipids, minerals vitamins and enzymes. Chapters on color, flavor and texture help the student understand key factors in the visual and organoleptic aspects of food. The chapter on contaminants and additives provides an updated view of their importance in food safety. Revised chapters on beer and wine production, and herbs and spices, provide the student with an understanding of the chemistry associated with these two areas which are growing rapidly in consumer interest. New to this edition is a chapter on the basics of GMOs. Each chapter contains new tables and illustrations, and an extensive bibliography, providing readers with ready access to relevant literature and links to the internet where appropriate. Just like its widely used predecessors, this new edition is valuable as a textbook and reference. .
Ch-01: water -- Ch-02: Lipids -- Ch-03: Amino acids and protiens -- Ch-04: Carbohydrates -- Ch-05: Minerals -- Ch-06: Colors and food colorants -- Ch-07: Flavor -- Ch-08: Texture -- Ch-09: Vitamins -- Ch-10: Enzymes -- Ch-11: Fruits and Vegetables -- Ch-12: Herbs and Spices -- Ch-13: Beer and wine -- Ch-14: Transgenic crops -- Ch-15: Additives and contaminants.
Keywords: Food science; Food Science